Green fingers get professional - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
As part of a programme to improve horticultural production in Marsabit in northern Kenya, the Ministry of Agriculture and GTZ have organised training for 'horticulture service providers'. So far, eight people have been trained and are working, on a...